Konflik Lahan dan HAM : Telaah Efektivitas Perlindungan Hukum terhadap Hak Masyarakat Adat di Indonesia dari Praktik Land Grabbing dan Green Grabbing - Sonia Yolanda; Muhammad Naufal Hakim; Zahvirah Ayudiah Pratiwi; Syamsu Adriyan Sahidin; Muhammad Fadhlurrahman; Muhammad Naufal Farras Gumay (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This research is aimed at examining how to protect the rights of indigenous peoples from several practices through a review of legislation. Regulations on customary law communities have long been regulated in Indonesian law, including the constitution. However, overlapping regulations due to conflicts of interest between the government and investors hinder the protection of their rights. Governments are often involved in land and natural resource grabbing, known as land grabbing and green grabbing. This practice triggers complex conflicts that are detrimental and ignore the rights of indigenous peoples. The conflict is rooted in the government's negligence in drafting harmonized rules that should really protect customary law communities.